THE POLITICAL REGIME IN KAZAKHSTAN: ITS CURRENT STATE AND POSSIBLE FUTURE - SHKEL, Stanislav (CENTRAL ASIA AND THE CAUCASUS, 2009)
Political science defines “political regime” in a variety of ways, yet only two of the definitions are commonly accepted. One of them relies on the political and legal, or institutional, approach, while the other is based on sociology. However, they agree when it comes to an understanding of the diverse relations between the government and society. Those wishing to define any specific political regime should proceed from its institutional design and corresponding political practice (observance of constitutional norms, freedoms and rights); the degree of public involvement in decision-making at the state level; the degree and possibility of competition between the government and the opposition; and the role of open coercion and enforcement in state governance.1 The majority of Russian political scientists, studying the transformations in the post-Soviet expanse, concentrate on political actors and institutions and the mode of their interaction responsible for the structure of power relations. V. Ghelman, for example, who identifies actors, institutions, resources, and strategies as the main independent variables, has described a political regime as the “sum-total of actors involved in a political process, institutions of political power, and the resources and strategies used to gain and retain power.”2 R. Turovskiy seems to agree with the above. He describes a political regime as the “sum-total of political actors (including their methods of governance, resources, aims and strategies) and institutions (interpreted both as organizations and the norms and rules of the game) operating on a certain territory.”3